Homeless bird - Whelan, Gloria (New York : HarperCollins Publishers, 2000)
When thirteen-year-old Koly enters into an ill-fated arranged marriage, she must either suffer a destiny dictated by India's tradition or find the courage to oppose it.(Gr.5-8)
800
Accelerated Reader AR
Keywords: Courage -- Fiction; Young women -- India -- Fiction; Arranged marriage -- India -- Fiction; India -- Fiction